2011
DOI: 10.1038/hr.2011.127
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of circulating superoxide dismutase activity in type 2 diabetic patients with microalbuminuria and its modulation by telmisartan therapy

Abstract: Growing evidence indicates that oxidative stress induced by excessive superoxide has a central role in the pathogenesis of diabetic nephropathy (DN). Telmisartan, one of the currently available angiotensin II type 1 receptor blockers (ARBs), has been shown to exert a more powerful proteinuria (albuminuria) reduction in patients with DN, but whether the prominent renoprotective effect of telmisartan is mediated through enhancing antioxidant defense capacity and reducing oxidative stress has not been fully eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…ARBs are widely used for the amelioration of proteinuria (albuminuria) in patients with DN, and provide more beneficial effects especially in incipient DN stage as shown in the INNOVATION study [31,32]. A large body of evidence from experimental studies and our clinical study suggests that ARBs exert greater anti-oxidative effects and ameliorate diabetic and oxidative renal injury [30,[33][34][35]. Moreover, a recent experimental study has reported that DPP-4 inhibition on top of angiotensin II type 1 receptor blockade provides more powerful renoprotective effects through highly reducing oxidative stress in diabetic kidney [4].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…ARBs are widely used for the amelioration of proteinuria (albuminuria) in patients with DN, and provide more beneficial effects especially in incipient DN stage as shown in the INNOVATION study [31,32]. A large body of evidence from experimental studies and our clinical study suggests that ARBs exert greater anti-oxidative effects and ameliorate diabetic and oxidative renal injury [30,[33][34][35]. Moreover, a recent experimental study has reported that DPP-4 inhibition on top of angiotensin II type 1 receptor blockade provides more powerful renoprotective effects through highly reducing oxidative stress in diabetic kidney [4].…”
Section: Discussionmentioning
confidence: 97%
“…We have recently reported that renal oxidative stress is highly produced in the incipient DN stage, but not the normoalbuminuric stage, and that the incipient DN stage is more suitable than other stages for antioxidative intervention [30]. Treatment with DPP-4 inhibitors which have higher selectivity and stronger inhibitory activity for DPP-4 is expected to contribute greatly to the amelioration of renal oxidative stress and albuminuria in patients with incipient DN.…”
Section: Discussionmentioning
confidence: 99%
“…A recent clinical study has shown it to be more effective in renoprotection as compared to other ARB class of drugs like losartan and valsartan owing to the difference in their intrinsic pharmacokinetic and physiochemical properties [160]. Furthermore, a number of properties like the best binding affinity to Ang II type 1 receptors, the maximum plasma halflife and the highest lipophilicity among the presently available…”
Section: Telmisartanmentioning
confidence: 99%
“…The effects of plant extracts on diabetic patients have shown to reduce the level of ROS, blood glucose level along with the improvement of antioxidants activity [113,191]. Studies on human also indicate the renal protective effect of above mentioned drugs by decreasing the expression of TGF-β and AGE, thereby preventing albuminuria [160,192]. But to increase the efficacy of above mentioned molecules, a targeted drug delivery system is essential and that is lacking in present scenario.…”
Section: Current Status and Future Prospect Of Antioxidant Therapies mentioning
confidence: 99%
“…The knowledge of the association of microalbuminuria with oxidative stress could be of therapeutic interest. Although the use of antioxidants and supplementation of enzyme cofactors can be conceivably envisaged, the prominent renoprotective effect of angiotensin II type 1 receptor blocker (ARB) Telmisartan in type 2 diabetes, a condition associated with microalbuminuria as SCA has been reported to be mediated through enhancing antioxidant defense capacity and reducing oxidative stress [6]. Unfortunately, data on oxidative stress in SCA patients with and without microalbuminuria are very scare in Africa, a setting where SCA is prevailing [710].…”
Section: Introductionmentioning
confidence: 99%